2021
DOI: 10.1080/10717544.2021.1895904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transgene expression characteristics and DNA vaccination against melanoma metastasis of an intravenously injected ternary complex with biodegradable dendrigraft poly-L-lysine in mice

Abstract: We developed a biocompatible splenic vector for a DNA vaccine against melanoma. The splenic vector is a ternary complex composed of plasmid DNA (pDNA), biodegradable dendrigraft poly-L-lysine (DGL), and c-polyglutamic acid (c-PGA), the selective uptake of which by the spleen has already been demonstrated. The ternary complex containing pDNA encoding luciferase (pCMV-Luc) exhibited stronger luciferase activity for RAW264.7 mouse macrophage-like cells than naked pCMV-Luc. Although the ternary complex exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Actually, pre-administration of clodronate liposomes decreased gene expression of γ-PGA coated complexes in the spleen. This result indicated that γ-PGA coated complexes were partly taken by the macrophages in the spleen [23]. Matsuo K. et al have also reported that γ-PGA coated nanoparticles efficiently delivered entrapped antigenic proteins into DCs and presented antigens to DCs via major histocompatibility complex class I and II molecules [24].…”
Section: Discussionmentioning
confidence: 86%
“…Actually, pre-administration of clodronate liposomes decreased gene expression of γ-PGA coated complexes in the spleen. This result indicated that γ-PGA coated complexes were partly taken by the macrophages in the spleen [23]. Matsuo K. et al have also reported that γ-PGA coated nanoparticles efficiently delivered entrapped antigenic proteins into DCs and presented antigens to DCs via major histocompatibility complex class I and II molecules [24].…”
Section: Discussionmentioning
confidence: 86%
“…Their in vivo instability, however, poses a fundamental challenge to the field [ 50 , 51 ]. The inclusion of polyanionic component to DNA/cationic peptide complexes may prevent a serum-mediated inhibition of transfection, both in vitro and in vivo [ 39 , 40 , 46 ]. In this study biodegradable cystine-cross-linked-poly-L glutamic acid was added to the pDNA/arginine-histidine-cysteine-rich peptide-based polyplexes.…”
Section: Resultsmentioning
confidence: 99%
“…Kurosaki et al reported that, after intravenous injection, γ-polyglutamic acid-coated cationic complexes of DNA and poly-L-arginine or poly-L-lysine showed high gene expression in the spleen [ 44 ]. Kodama et al demonstrated that after γ-PGA-coated dendrigraft poly-L-lysine-based polyplexes were intravenously injected into mice, they displayed high transfection efficiency (mainly in the spleen) and negligible liver toxicity [ 45 , 46 ]. Importantly, DNA vaccination using the ternary vehicles suppressed the growth of melanoma and lung metastasis in mice by activating the systemic immunity, proving the efficiency and safety of ternary PGA-coated polypeptide complexes for clinical gene therapy [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various nanoparticles have been applied to deliver DNA-based vaccines and promote antitumor immune responses, including polymeric nanoparticles, liposomes, silica nanoparticles, bisphosphonate-modified calcium phosphate nanoparticles, gold nanoparticles, virus nanoparticles, and carbon nanotubes [ 72 , 73 , 74 ]. Liposomes are one of the well-recognized nanoparticle vaccine delivery platforms, which are easy to construct by altering the composition, surface of lipid, and other important properties [ 75 , 76 , 77 ]. Liposomes can not only augment the immunogenicity of special antigens for cancer DNA vaccines, but they also improve the therapeutic efficacy.…”
Section: Dna Vaccine Delivery Platformsmentioning
confidence: 99%